Selecting treatment method for ovarian masses in children - 24 years of experience - Justyna Łuczak; Maciej Bagłaj (BMC, 2017)
Abstract Background Epidemiology and pathology of ovarian tumors in the pediatric population are very different of these encountered in women. Few attempts have been made to analyze the whole spectrum of ovarian pathology in children, and only some of them included series of more than 200 cases. We performed a retrospective analysis of clinical and diagnostic aspects of ovarian tumors and tumor-like lesions in girls in order to identify the characteristics associated with malignancy with an attempt to elaborate a clinical management algorithm. Results The study group comprised 214 patients operated on for ovarian tumor in years 1991-2014 at the pediatric surgical center. Non-neoplastic ovarian lesion was diagnosed in 127 females. Sixty-five patients had a benign tumor and 22 had a malignant lesion. Abdominal pain was the most common symptom in the non-malignant lesion group. Patients with ovarian malignancy presented predominantly with abdominal distension and palpable mass. In the non-malignant group imaging studies revealed cystic lesion in 124 patients (68.89%) and solid mass in 10 (5.55%). Malignant lesion showed a solid or mixed structure in all cases. Positive tumor markers were noted in 14 (13.7%) patients with a benign lesion and in 14 (70%) with ovarian malignancy. Large lesions were found in 77.3% of girls with a malignant mass, while only in 32.8% of patients with a benign lesion (p < 0.001). In the group of solid tumors positive tumor marker results occurred more frequently in patients with diagnosed malignant tumors (p < 0.05). Positive tumor markers, large size of the lesion and age below 14 years were independent variables differentiating malignant tumors from non-malignant lesions (p = 0.00000). Conclusions Predominantly solid structures noted on imaging studies, large dimension and positive tumor markers are clinical predictors of malignancy. A diagnosis of purely cystic lesions with negative markers or of a small size should be an indication for a gonad-sparing procedure. Treatment guidelines for ovarian lesions in children should be established on the basis of multicenter prospective studies and introduced as soon as possible in order to improve and unify the ovarian preservation rates across the pediatric surgical centers.